Tantangan Kontemporer Bangsa Indonesia: Respon Dunia Pendidikan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The problems of the educational policy in response to the contemporary challenge in Indonesia are coincided with three issues: ( I) the educational response to globalisation and market liberalisation, (2) the educational response to territorial autonomy, and (3) the educational institution capacity in improving the educational quality. In the last 30 years, education system in Indonesia has been too centralized, uniformed and had only single standard. It tended to neglect the diversity of communities, areas and cultures. To resolve urrent issues, education has to be understood as a societal responsibility, encompassing governments, families, communities and organizations. It requires commitment and participation of all, that all elements of communities should be regarded as 'educational instruments'. In relation to the issues in local autonomy policy, attention has to be given to some principles in education: I) it should not only be elucidated as a power shift from the central to the local government, but it should be linked closely to democracy, 2) flexibility in implementing any government policy, and (3) in response to the global issues, local governments have to be able to build collaborative networks with institutions in foreign countries. With regards to institutional capacity building, local stakeholders must work together in a "School Based Management" system.